2020
DOI: 10.1007/s11274-020-02935-x
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional comparison of Saccharomonospora azurea strains in terms of primycin producing ability

Abstract: Emerging and re-emerging microbial pathogens, together with their rapid evolution and adaptation against antibiotics, highlight the importance not only of screening for new antimicrobial agents, but also for deepening knowledge about existing antibiotics. Primycin is a large 36-membered non-polyene macrolide lactone exclusively produced by Saccharomonospora azurea. This study provides information about strain dependent primycin production ability in conjunction with the structural, functional and comparative g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…In this study we also focused on the identification of biosynthetic gene clusters (BGCs) in the genome of the analyzed strains of Saccharomonospora . Only a few previous reports mining BGCs in this genus have been published so far ( Yamanaka et al, 2014 ; Schorn et al, 2016 ; Reynolds et al, 2018 ; Kovács et al, 2020 ), which investigated the genomes of Saccharomonospora sp. CNQ-490, Saccharomonospora sp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study we also focused on the identification of biosynthetic gene clusters (BGCs) in the genome of the analyzed strains of Saccharomonospora . Only a few previous reports mining BGCs in this genus have been published so far ( Yamanaka et al, 2014 ; Schorn et al, 2016 ; Reynolds et al, 2018 ; Kovács et al, 2020 ), which investigated the genomes of Saccharomonospora sp. CNQ-490, Saccharomonospora sp.…”
Section: Discussionmentioning
confidence: 99%
“…Most important, several BGCs showed no match to any already discovered compound or had a low similarity to known molecules, in particular clusters related to the synthesis of acarviostatin I03/acarviostatin II03/acarviostatin III03/acarviostatin IV03, allocyclinone, amycolamycin A/amycolamycin B, anthracimycin, apoptolidin, arsenopolyketides, collismycin A, concanamycin A, desosamine, ebelactone, ECO-02301, enduracidin, ficellomycin, friulimicin, herboxidiene, hygrocin A/hygrocin B, indanomycin, kedarcidin, mediomycin A, octacosamicin, oxazolomycin, PM100117/PM100118, rabelomycin, ralsolamycin, retimycin, sanglifehrin A, selvamicin, skyllamycin and tiancimycin, which shared less than 50% of the genes with the BGCs in the MIBiG database ( Table 3 ), and they are probably involved in the synthesis of new bioactive compounds with promising clinical and biotechnological applications. In spite of the large genomic potential of Saccharomonospora BGCs to synthetize bioactive molecules, a literature search shows that only a few bioactive compounds (primycin, taromycin, and saccharomonopyrones A-C) have been isolated so far from members of the genus Saccharomonospora ( Yamanaka et al, 2014 ; Yim et al, 2017 ; Reynolds et al, 2018 ; Kovács et al, 2020 ) and, therefore, a more comprehensive screening to isolate more biomolecules that can be synthetized by members of this genus should be carried out. Primycin is known to be produced only by strains of the species S. azurea ( Kovács et al, 2020 ), which coincides with our genomic data ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the strain Kh3 was identified as S. azurea, which is a rare species from Actinomycetes. This species is a fascinating species that has garnered attention due to its potential in the production of antibacterial activity, particularly against Gram-positive bacteria that have developed resistance to multiple drugs [40,41]. Feiszt et al [42] conducted a re-evaluation of the antibacterial activity of S. azurea against various bacterial pathogens in vitro.…”
Section: Discussionmentioning
confidence: 99%